COL11A1 gene is associated with limbus vertebra in gymnasts - Koyama, K.; Nakazato, K.; Min, S; Gushiken, K.; Hatakeda, Y.; Seo, K.; Hiranuma, K. (International Journal of Sports Medicine, 2012)
Several studies have shown higher frequencies of radiological abnormalities among gymnasts. Recently, the gene encoding the ?1 chain of type XI collagen, (COL11A1) (rs 1676486), was associated with lumbar disc herniation in the Japanese population. We hypothesized that there was a significant relationship between abnormal magnetic resonance imaging (MRI) findings of the lumbar spine and the COL11A1 4603C/T gene polymorphism in collegiate gymnasts. Our study participants included 103 Japanese collegiate gymnasts (70 men and 33 women). Radiological abnormalities were evaluated using T1- and T2-weighted MRI. Genotyping for COL11A1 was performed for all the participants. By using logistic regression analysis, we observed significant associations between limbus vertebra and age (adjusted odds ratio=0.51, 95% confidence interval: 0.27-0.96), sporting experience (adjusted odds ratio=1.49, 95% confidence interval: 1.14-1.94), and a TT genotype (adjusted odds ratio=7.83, 95% confidence interval: 1.33-46.03). We conclude that a TT genotype of COL11A1 polymorphism may be a significant risk factor for limbus vertebra in Japanese collegiate gymnasts.